Analysis of the Influence of Fundamental Macro and Fundamental Micro to Discolure of Corporate Social Responsibility, Ownership Structure, Financial Performance, Going Concern Audit Opinion and Value of the Firm at State-Owned Enterprises in Indonesia - Hwihanus, Tan; Ratnwati, Tri; Yuhertiana, Indrawati (Archives of Business Research, 2018)
This study aims to examine and analyze the relationship between the variables of micro-finance, macro fundamental fundamentals of disclosure of corporate social responsibility, ownership structure, financial performance, going concern audit opinion and the value of the firms in State-Owned Enterprises listed on the Indonesia Stock Exchange. Research population at 20 State-Owned Enterprises listed on Indonesia Stock Exchange. This research method uses purposive sampling with 12 companies in 2010 - 2016. Techniques of data analysis in this study using Partial Least Square (PLS) consists of Inner model, Outers model and Weight relation. The test results showed that all tested variables were influenced by other variables and were significant with t-statistics above 5% significant level with t-table 1,960 except macro fundamental against ownership structure showing the effect of 0.0031421 and t-statistics of 1.327460 so the research hypothesis (H3) of macro fundamentals have a not significant effect on the ownership structure is rejected whereas hypotheses other research accepted.